Chiloschista densiflora (Orchidaceae), a distinctive species newly recorded from Xizang, China - Wen, Ying-Ying; Ma, Chong-Bo; Zhang, Tian-Kai; Wang, Xi-Long; Chen, Wen-Shuai; Yang, Bo-Yun; Jin, Xiao-Hua (Phytotaxa, 2023)
Chiloschista densiflora (Orchidaceae), a new record of flora of China, is described and illustrated based on materials from Motuo, Xizang. Morphologically, Chiloschista densiflora is characterized by middle lobe with a pubescent callus ranging from base to apex, two conical calli at base, short and stocky column.